1989
DOI: 10.3168/jds.s0022-0302(89)79127-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sodium Bicarbonate or Sodium Sesquicarbonate on Lactating Holsteins Fed a High Grain Diet

Abstract: Fifteen Holstein cows, 35 to 70 d postpartum, were assigned to five 3 x 3 Latin squares. Treatments were: control (60% concentrate, 40% corn silage, DM basis) or control supplemented with either .71% sodium bicarbonate or .65% sodium sesquicarbonate, DM basis. Orthogonal contrasts compared the effect of both buffered diets versus the control diet, and the effect of sodium bicarbonate supplementation vs. sodium sesquicarbonate supplementation. There were no differences among treatments for milk yield (34.9 kg/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
10
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 12 publications
3
10
0
2
Order By: Relevance
“…The effects of SB on DMI have been inconsistent in previous studies. While some work has reported no effect of SB on DMI (Hart and Polan 1984;Coppock et al 1986;Ghorbani et al 1989), other researchers have reported that dietary buffers improved feed intake and increased animal performance (Fulton et al 1979b;Solorzano et al 1989;Zinn 1991). Keunen et al (2003) reported that offering free choice SB to dairy cows with ruminal acidosis did not increase DMI, similar to our observations.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The effects of SB on DMI have been inconsistent in previous studies. While some work has reported no effect of SB on DMI (Hart and Polan 1984;Coppock et al 1986;Ghorbani et al 1989), other researchers have reported that dietary buffers improved feed intake and increased animal performance (Fulton et al 1979b;Solorzano et al 1989;Zinn 1991). Keunen et al (2003) reported that offering free choice SB to dairy cows with ruminal acidosis did not increase DMI, similar to our observations.…”
Section: Discussionsupporting
confidence: 86%
“…When mixed into the ration, dietary buffers such as sodium bicarbonate (SB) can elevate ruminal pH (Ghorbani et al 1989;Solorzano et al 1989;Zinn 1991), although not always (Russell et al 1980;Hart and Polan 1984). Bicarbonate, the primary buffer in saliva and ruminal fluid, is a strong neutralizer of reductions in ruminal pH (Kohn and Dunlap 1998).…”
mentioning
confidence: 99%
“…Lactate concentrations were not effected in the BUFfed heifers, consistent with sodium bicarbonate-fed dairy cattle (Kilmer et al, 1981;Kennelly et al, 1999), but were numerically lower than the control and MT groups. The decrease in ammonia concentration may suggest the BUF reduced protein degradation; however, ammonia concentrations were not affected in sodium bicarbonate-fed cattle (Solorzano et al, 1989;González et al, 2008).…”
Section: Discussionmentioning
confidence: 93%
“…It has been shown to effectively neutralize rumen acidity and stabilize rumen pH (Thomas et al, 1984;Solorzano et al, 1989) and to improve the efficiency of fiber digestion, microbial protein synthesis (Rogers et al, 1982), and OM utilization (Mackie and White, 1990). It could furthermore increase milk fat content and feed intake (Enemark, 2008).…”
Section: Introductionmentioning
confidence: 98%